2007
DOI: 10.1200/jco.2007.25.18_suppl.5014
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant and adjuvant androgen deprivation (ADT) with external beam irradiation (RT) for locally advanced prostate cancer: 6 months versus 3 years ADT—Results of the randomized EORTC Phase III trial 22961

Abstract: 5014 Background: After EORTC trial 22863, 3 years of endocrine treatment has become standard adjuvant treatment to RT for locally advanced prostate cancer. EORTC 22961 tests if similar survival can be achieved in patients who underwent EBRT (to 70 Gy) and 6 months of combined ADT without further ADT (SADT arm) as in patients with 2.5 years of further treatment with luteinizing hormone-releasing hormone agonist monotherapy (LADT arm). Methods: Eligible patients had T1c-2b N1–2 or pN1–2, or T2c-4 N0–2 (UICC 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…One paper reported the results of 2 trials8; 1 was excluded because it was designed to compare HT duration without an exclusive RT arm. Three additional RCTs were excluded for the same reason 23‐25. Seven and 5 RCTs, respectively, were evaluable for biochemical failure (3956 patients, data lacking for 179 patients) and clinical progression‐free survival (4020 patients, data lacking for 2 RCTs8, 13).…”
Section: Resultsmentioning
confidence: 99%
“…One paper reported the results of 2 trials8; 1 was excluded because it was designed to compare HT duration without an exclusive RT arm. Three additional RCTs were excluded for the same reason 23‐25. Seven and 5 RCTs, respectively, were evaluable for biochemical failure (3956 patients, data lacking for 179 patients) and clinical progression‐free survival (4020 patients, data lacking for 2 RCTs8, 13).…”
Section: Resultsmentioning
confidence: 99%
“…Another possible explanation could be that the ADT duration for the high and extreme risk groups was insufficient. Prolonging the duration of ADT appears to benefit patients with a higher chance of relapse following EBRT [ 18 , 19 ]. A previous analysis from our institution also demonstrated an advantage to prolonged, rather than shorter ADT duration (6 months versus 12 versus 24 months) in patients with localized disease and a PSA above 20 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal duration of HT is unclear. Two randomized trials have shown that, compared with six months of HT together with conventional radiotherapy 70Gy, 28 months(137) or 36 months(138) improves PCa-specific outcomes. Results from another study suggest that treatment for more than six years may benefit some patients(139).D'Amico et al showed recently that even though radiotherapy + six months of HT improved overall survival compared with radiotherapy alone for localized unfavorable-risk PCa, this was not true for a subgroup of patients with moderate to severe comorbidity.…”
mentioning
confidence: 99%